Tingkat Partisipasi Anggota Kelompok Tani Hutan Giri Jaya - Arneta, Arneta; Hendrawan, Hendrawan (Jurnal Dimamu, 2025)
The success ofiifarmeriigroupsiidependsiion the active participationoof farmers as group members. Therefore, this research aimsito determineitheiilevel ofiimember participationiinigroup activities and identify theiiobstacles that may affect the level of participation. The data analysis used is a type of quantitative descriptive analysis with a total of 20 respondents, representingiiall membersiiofiithe farmeriigroup. Theimethod usediiis aicaseistudy, focusingionithe Kelompok Hutan Tani (KTH)iGiri Jayaiin DesaiiNagrog, KecamataniCicalengka, KabupateniBandung. The variables measurediin this researchiare theiparticipation of farmer group membersin the planning,iimplementation, evaluation, andibenefits stages, usingia Likertiscale. Theiresearch resultsishow that theiiparticipationiof farmer group members is in the High category. Specifically, planning is in the medium category with a scoreiof 21.65; implementation is iniithe highiicategory withia score of 25.3; evaluation is inithe mediumicategoryiwith a score ofi22; and benefits are in theiihigh categoryiiwith aiscore of 27.8.iiThe total overalliscore is 96.75, placing it inithe highicategory.